Guarda municipal de Mossoró: análise comparativa entre as atribuições definidas na lei complementar nº 037 e no estatuto geral das guardas municipais - Paiva, José Rodolfo Cavalcante de (Universidade Federal Rural do Semi-Árido, 2019)
The escalation of violence and crime rates has contributed to municipal managers becoming more and more protagonists in terms of public security policies. One of the most evident forms of this protagonism has been the creation and structuring of Municipal Civil Guards, which in recent decades have been contributing proficiently to the intervention in this issue from a local perspective. However, for many years, the guards act without ample legal security, basing their actions on municipal devices, as in the case of Mossoró, where the Civil Guard had its competencies defined through Complementary Law No. 037/2009. Only in 2014, with the approval of the General Statute of the Municipal Guards, Federal Law 13,022, did this institution consolidate its administrative and operational competencies at the national level through this legal provision that brought legal security to the civil guards of all municipalities in Brazil. The main objective of this work is to understand the attributions of the Municipal Civil Guard of Mossoró delimited by Complementary Law No. 037/2009 and, subsequently, by the General Statute of Municipal Guards, pointing out similarities, differences and advances in the applicability of both from the perspective of legality. In order to achieve this objective, an extensive exploratory research was carried out based on the selection, review and bibliographic analysis of works of Law that deal with the theme. In the end, it was found that the Statute was important to support the actions of the GCM at the local level, in addition to adding other important competencies in the focus of its institucional actions.
Keywords: Guarda Municipal; Competências; Lei 13.022/14; Lei 037/2009; Municipal guard; Legal powers; Law 13.022/14; Law 037/2009; CIENCIAS SOCIAIS APLICADAS::DIREITO